PP.02.26: A HOME-BASED PROGRAM MME OF PHYSICAL ACTIVITY CENTERED ON "FAST WALKING" IMPROVES BLOOD PRESSURE VARIABILITY IN ESSENTIAL HYPERTENSIVES. (June 2015) - Di Raimondo, D.; Tuttolomondo, A.; Butta', C.; Miceli, G.; Pinto, A.
Abstract : Objective: Blood pressure (BP) values fluctuate continuously. Blood pressure variability (BPV), that is the standard deviation around the mean of the measurements collected using an ambulatory blood pressure measurement (ABPM) device, has attracted increasing interest in clinicians. An increased variability of 24 hours BP has been associated with increased progression of organ damage and a higher incidence of vascular events. As well, recent retrospective analyses of published trial data have concluded that antihypertensive drug classes differ in their effects on BPV, thereby exerting a different reduction of cardio- and cerebro-vascular risk. Aim of our study was to ascertain whether aerobic exercise of moderate intensity was able to reduce 24 hours BP variability. Design and method: were enrolled 158 subjects affected by essential hypertension. Physical activity program proposed to patients consisted of 24 weeks of fast walking. Every subject was requested to walk for one hour/day, at a speed of 5–6 km/hour, individually fit during the preliminary procedures of the study. Ascertainment of the number of steps, of the total distance walked and of the mean velocity was made through a podometer provided with a 2 axis accelerometer (OMRON step counter type Walking Style II). Results: Patients walked about 9, 000 steps per day (9.150 ± 1440), for a medium total distance covered every day of 5640 ± 450 meters. Variation of BPV values, obtained through two ABPM measurements, before and after the domiciliary training period are the following: 24 hours PAS variability: 16.82 mmHg vs 14.12 mmHg (P < 0.001), 24 hours PAD variability 11.86 mmHg vs 10.16 mmHg (P < 0.001), diurnal PAS variability 17.86 vs 15.47 mmHg (P < 0.001), diurnal PAD variability 13.43 vs 11.87 mmHg (P < 0.001), nocturnal PAS variability 10.47 vs 7.79 mmHg (P < 0.001), nocturnal PAD variability 8.44 vs 6.58 mmHg (P < 0.001). The results maintained the statistical significance also after correction of the variation for the different antihypertensive therapies, the weight loss, sex and other confounding factors. Conclusions: A home based program of physical activity improves BP variability in essential hypertensives.